An investigation of the impact of the climate change on river deltas: Case study: The delta of r. Pinios (Thessaly, Greece) - concept and preliminary results on surface water environmental state - Poulos, S.; Alexopoulos, J.; Dassenakis, M.; Kotsopoulos, S; Lazogiannis, K.; Matiatos, J.; Paraskevopoulou, V; Sifnioti, D.; Ghionis, G.; Alexiou, I; Panagopoulos, A (13th International Conference on Environmental Science and Technology, 2013)
The scope of the research project is to investigate the consequences of climate change on deltaic plains, as one of the most vulnerable coastal and wealth-producing ecosystems. The Pinios river delta, located in the region of Thessaly (Greece) has been selected as a case study, as one of the largest Greek rivers with very limited flow controls. But, despite the fact that deltaic plain is part of the NATURA network, human intervention continuous to occur at an increasing rate. The main objectives of the project are to: (i) study the relative contribution of fluvial fluxes (water/sediment), nearshore hydrodyanmics and climate conditions in the formation and evolution of deltas; (ii) evaluate the impact of human activities in the evolution of the River Pinios delta (e.g., alteration of riverine fluxes, agricultural pollution, over-pumping of the aquifer); (iii) assess and to evaluate quantitatively changes in the deltaic environment for different climate change scenarios, i.e. water balance, issues of water quality, desertification, coastal erosion, inundation; (iv) investigate the interaction between natural processes and parameters associated with socio-economic development and use; (v) develop Sustainable Development Strategies for the natural deltaic system, in order to mitigate the consequences of the climate change, towards a better management of the wealthproducing resources (i.e. fresh water yield); (vi) contribute to the training of young scientists in environmental issues, related to the impact of the climate change on coastal environments; and (vii) disseminate science based management strategies to the local and scientific communities. During the first phase of project implementation, the study of the surface and ground water and their interrelationship is investigated through: (i) the climatological conditions of the deltaic plain and the drainage basin; (ii) the determination of the subsurface geological/stratigraphical information provided by geophysical data; (iii) surface and water fluxes estimated on monthly measurements (quantitative and qualitative) of river flow and phreatic water table.